# Pre-cal

posted by .

use mathematical induction to prove that 1^2 + 2^2 + 3^2 + ... + n^2 = n(n+1)(2n+1)/6 for all positive integral values of n.

My work: n=1: 1(1+1)(2(1)+1)/6 = 1(2)(3)/6 = 6/6 = 1.

1^2+2^2+3^2...(n-1)^2+n^2= [(n-1)(n-1)+2n(n-1)+1]/6 = 2n^3+3n^2+n/6 = n(2n=1)(n+1)/6 = n(n+1)(2n+1)/6. Since Sn is valid for n=1, it is also valid for n=2, n=3, etc.

The teacher marked this as wrong but this followed the example provided by the book. Where did I go wrong?

• Pre-cal -

Step 1
show it to be true for n=1
LS = 1^2 = 1
RS = (1)(2)(3)/6 = 1, checks out

Step 2
Assume it is true for n=k
that is..
1^2 + 2^2 + 3^2 + ... + k^2 = k(k+1)(2k+1)/6

Step 3
is it then true for n = k+1 ??
or
is 1^2 + 2^2 + 3^2 + ... + k^2 + (k+1)^2 = (k+1)(k+2)(2k+3)/6 ??
from Step 2 the sum of terms to the end of k^2 = k(k+1)(2k+1)/6

then
LS = k(k+1)(2k+1)/6 + (k+1)^2
= (k(k+1)(2k+1) + 6(k+11)^2)/6
= (k+1)(k(2k+1) + 6(k+1))/6
= (k+1)(2k^2 + k + 6k + 6)/6
= (k+1)(k+2)(2k+3)/6
= RS

Q.E.D.

Where you not shown the 3step process of an induction proof?

## Similar Questions

1. ### PRE CAL SEQUENCES

Given the following finite sum 1/(1*2)+1/(2*3)+1/(3*4)+1/(4*5)+....+1/(n(n+1)) a) Find the first 5 partial sums b) Make a conjecture for a formula for the sum of the first n terms c) Use mathematical induction to prove your formula
2. ### Calculus

Use mathematical induction to prove that each proposition is valid for all positive integral values of n. 5^n + 3 is divisible by 4.
3. ### Math - Mathematical Induction

3. Prove by induction that∑_(r=1)^n▒〖r(r+4)=1/6 n(n+1)(2n+13)〗. 5. It is given that u_1=1 and u_(n+1)=3u_n+2n-2 where n is a positive integer. Prove, by induction, that u_n=3^n/2-n+1/2. 14. The rth term of …
4. ### AP Calc

Use mathematical induction to prove that the statement holds for all positive integers. Also, can you label the basis, hypothesis, and induction step in each problem. Thanks 1. 2+4+6+...+2n=n^2+n 2. 8+10+12+...+(2n+6)=n^2+7n
5. ### Calculus

Use mathematical induction to prove that the statement holds for all positive integers. Also, label the basis, hypothesis, and induction step. 1 + 5 + 9 + … + (4n -3)= n(2n-1)
6. ### Math

Use mathematical induction to prove that 2^(3n) - 3^n is divisible by 5 for all positive integers. ThankS!
7. ### pre-calc

Use mathematical induction to prove that the statement is true for every positive integer n. Show your work. 2 is a factor of n2 -n+2
8. ### pre calc

Use mathematical induction to prove that the statement is true for every positive integer n. Show your work. 2 is a factor of n2 - n + 2
9. ### pre calc

Use mathematical induction to prove that the statement is true for every positive integer n. Show your work. 2 is a factor of n2 - n + 2
10. ### Mathematical Induction

Use mathematical induction to prove that the following is true. 8+11+14...+(3n+5)=1/2n(3n+13), for all n in the set of natural numbers.

More Similar Questions